Black esophagus: acute esophageal necrosis in fatal haloperidol intoxication - Hejna, Petr; Ublová, Michaela; Voříšek, Viktor (Journal of forensic sciences, 2013)
Herein, we present a case of 53-year-old psychotic woman with acute esophageal necrosis (black esophagus), who was found lying on the floor in the living room of her flat. Pillboxes of antipsychotic drugs were located in the bin. External examination of the body was unremarkable. On internal examination, we found acute esophageal necrosis. Histologically, there was complete epithelial necrosis with focal involvement of muscularis mucosae, dense infiltrate of leukocytes, and ulcerations without any viable cells. There was no evidence of underlying organic diseases or trauma. Toxicological analysis revealed a fatal blood level of antipsychotics (haloperidol, zotepine, and chlorprothixene). Death of the deceased was attributed to fatal intoxication with three various types of antipsychotics. As far we know, this is the first described association between so-called black esophagus and fatal blood level of neuroleptics.
Keywords: Dibenzothiepins; chlorprothixen; Female; Mucous Membrane; antipsychotika; Antipsychotic Agents; black esophagus; ženské pohlaví; autopsy; fatal intoxication; suicide; haloperidol; lidé; neuroleptics; nekróza; Haloperidol; Forensic Pathology; acute esophageal necrosis; Necrosis; forensic science; Chlorprothixene; Esophagus; sliznice; lidé středního věku; ezofágus; Middle Aged; dibenzothiepiny; soudní patologie; Humans